2010
DOI: 10.1093/jac/dkq495
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of capuramycins to enhance antibacterial activity

Abstract: Conjugation of capuramycin analogues with AUA or DEC enhanced in vitro activity, extended the spectrum of activity in Gram-positive bacteria and increased intracellular activity against H37Rv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…1a) 5-8 . MraY-targeted natural products have gained attention because of their in vivo efficacy against pathogenic bacteria including M. tuberculosis, methicillin-resistant S. aureus (MRSA), and vancomycin-resistant Enterococcus (VRE) 6,9-12 . Despite their promise, no antibacterial natural products that target MraY have been developed for clinical use, in part due to a lack of structural information on MraY catalysis and inhibition.…”
mentioning
confidence: 99%
“…1a) 5-8 . MraY-targeted natural products have gained attention because of their in vivo efficacy against pathogenic bacteria including M. tuberculosis, methicillin-resistant S. aureus (MRSA), and vancomycin-resistant Enterococcus (VRE) 6,9-12 . Despite their promise, no antibacterial natural products that target MraY have been developed for clinical use, in part due to a lack of structural information on MraY catalysis and inhibition.…”
mentioning
confidence: 99%
“…In murine model of tuberculosis, it has been shown that the treatment of mice with SQ609 is able to prevent weight loss in these mice. Furthermore, SQ609 has a prolonged therapeutic effect, extended by two weeks after termination of treatment, suggesting that SQ609 is well tolerated by mice and that this compound is not eliminated immediately following cessation of treatment [62]. SQ609 has good water solubility and has an antimycobacterial activity better than that of TB standard of care (1 --2 log 10 ) when administered in combination with INH, RIF, and PZA in murine models of TB.…”
Section: Sq609mentioning
confidence: 99%
“…In the same study, it was shown that treatment of mice for five weeks at 100 mg/kg with SQ641-TPGS micelles administered intraperitoneally reduced log 10 numbers of CFU in lungs from 8.09 to 6.15, while intravenous delivery of SQ641-TPGS micelles at 50 mg/kg, two times per week for four weeks decreased CFU numbers in lungs by 2.08 log [66]. More recently, a study involving murine macrophages infected with M. tuberculosis H37Rv strain has shown that acylation of SQ641 with amino undecanoic acid improves its intracellular bactericidal activity against M. tuberculosis H37Rv strain [62], suggesting that the modified version of SQ641 would be better than its original form for TB treatment.…”
Section: Sq641mentioning
confidence: 99%
“…As a result, it has poor intracellular and in vivo activity (11,12). To overcome these deficiencies, we earlier developed ␣-tocopheryl polyethylene glycol 1000 succinate (TPGS) soluble and micellar formulations of SQ641 (13,14).…”
mentioning
confidence: 99%
“…SQ641 was synthesized at Sequella, Inc., as described previously (7,12). INH, EMB, rifampin (RIF), and pyrazinamide (PZA) were purchased from Sigma-Aldrich, St. Louis, MO.…”
mentioning
confidence: 99%